EPIDEMIOLOGY AND RISK FACTORS FOR COLORECTAL RECTAL CANCER: AN UPDATE SYSTEMATIC REVIEW - Gajah, Supriyadi; Martupa Lumbantoruan, Johannes (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The global burden of colorectal cancer (CRC) has been rising rapidly with population growth, changes in demographics and Westernization of lifestyle habits. It was estimated to have 18.1 million new cancer cases, and 9.6 million deaths caused by cancer in year 2018. CRC is the third commonest diagnosed cancer and the second leading cause of cancer-related mortality. According to the World Health Organization (WHO) GLOBOCAN database, there are 1,849,518 estimated new CRC cases and 880,792 CRC-related deaths in 2018. Regional estimates show that among half of the new cases, deaths and 5-year prevalent cases were found in Asia. The aim: The aim of this study to show about epidemiology and risk factors for colorectal cancer. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 41 articles, whereas the results of our search on SagePub get 151 articles, on Google Scholar 2598 articles. Records remove before screening are 800, so we get 1990 articles fos screening. After we screened based on record exclude, we compiled a total of 12 papers. We included five research that met the criteria. Conclusion: Colorectal cancer is effectively preventable through primary and secondary prevention. Environmental risk factor mediation by the provision of information and encouragement of healthy behaviors, while striving for early diagnosis through appropriate screening tests, can lead to a reduction in the stagnant incidence and mortality rates.